Decitabine-induced apoptosis is derived by Puma and Noxa induction in chronic myeloid leukemia cell line as well as in PBL and is potentiated by SAHA - Brodská, Barbora; Otevřelová, Petra; Holoubek, Aleš (Molecular and cellular biochemistry, 2011)
Restoration of cellular apoptotic pathways plays a crucial role in cancer therapy strategies. In a broad spectrum of anticancer drugs, epigenetic effectors are in the center of interest mostly because of potential reversibility of their action. Methylation status of the cells is influenced by methyltransferase inhibitor 2-deoxy-5'-azacytidine (decitabine, DAC), but higher concentrations of this agent cause a DNA-damage. In our study, tumor supressor p53-apoptotic pathway was activated in decitabine-induced cell death. Expression of p53-inducible BH3-only apoptotic proteins Puma and Noxa was elevated and large activation of executive caspases was observed. The extent of acetylation in the cell is affected by histonedeacetylase inhibitor suberoylanilide hydroxamic acid (SAHA). Combination of SAHA with decitabine brought synergistic effect on apoptosis triggering in CML-T1 cell line, but apoptosis as well as necrosis occurred also in normal peripheral blood lymphocytes. Therefore, promising potential of such combined therapy calls for more detailed investigation of unwanted effects in normal cells.
Keywords: lymfocyty; chronická myeloidní leukemie; Drug Synergism; Up-Regulation; proteiny regulující apoptózu; Cells, Cultured; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Antimetabolites, Antineoplastic; Drug Evaluation, Preclinical; synergismus léků; azacytidin; Azacitidine; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; apoptóza; Hydroxamic Acids; Lymphocytes; Proto-Oncogene Proteins c-bcl-2; protoonkogenní proteiny; Proto-Oncogene Proteins; kultivované buňky; upregulace; Apoptosis Regulatory Proteins; Gene Expression Regulation, Leukemic; preklinické hodnocení léčiv; lidé; protinádorové antimetabolity; protoonkogenní proteiny c-bcl-2; Apoptosis; kyseliny hydroxamové; regulace genové exprese u leukemie